Monoclonal Antibody AP3 Binds Galactomannan Antigens Displayed by the Pathogens Aspergillus flavus, A. fumigatus, and A. parasiticus - Schubert, Max; Xue, Sheng; Ebel, Frank; Vaggelas, Annegret; Krylov, Vadim B.; Nifantiev, Nikolay E.; Chudobová, Ivana; Schillberg, Stefan; Nölke, Greta (Frontiers in Cellular and Infection Microbiology, 2019)
Aspergillus fumigatus and A. flavus are the fungal pathogens responsible for most cases of invasive aspergillosis (IA). Early detection of the circulating antigen galactomannan (GM) in serum allows the prompt application of effective antifungal therapy, thus improving the survival rate of IA patients. However, the use of monoclonal antibodies (mAbs) for the diagnosis of IA is often associated with false positives due to cross-reaction with bacterial polysaccharides. More specific antibodies are therefore needed. Here we describe the characterization of the Aspergillus-specific mAb AP3 (IgG1κ), including the precise identification of its corresponding antigen. The antibody was generated using A. parasiticus cell wall fragments and was shown to bind several Aspergillus species. Immunofluorescence microscopy revealed that AP3 binds a cell wall antigen, but immunoprecipitation and enzyme-linked immunosorbent assays showed that the antigen is also secreted into the culture medium. The inability of AP3 to bind the A. fumigatus galactofuranose (Galf )-deficient mutant ΔglfA confirmed that Galf residues are part of the epitope. Several lines of evidence strongly indicated that AP3 recognizes the Galf residues of O-linked glycans on Aspergillus proteins. Glycoarray analysis revealed that AP3 recognizes oligo-[β-D-Galf-1,5] sequences containing four or more residues with longer chains more efficiently. We also showed that AP3 captures GM in serum, suggesting it may be useful as a diagnostic tool for patients with IA.